2017
DOI: 10.3389/fpls.2017.00377
|View full text |Cite
|
Sign up to set email alerts
|

New Hypervariable SSR Markers for Diversity Analysis, Hybrid Purity Testing and Trait Mapping in Pigeonpea [Cajanus cajan (L.) Millspaugh]

Abstract: Draft genome sequence in pigeonpea offers unprecedented opportunities for genomics assisted crop improvement via enabling access to genome-wide genetic markers. In the present study, 421 hypervariable simple sequence repeat (SSR) markers from the pigeonpea genome were screened on a panel of eight pigeonpea genotypes yielding marker validation and polymorphism percentages of 95.24 and 54.11%, respectively. The SSR marker assay uncovered a total of 570 alleles with three as an average number of alleles per marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 49 publications
(68 reference statements)
8
35
0
Order By: Relevance
“…In the present study, the SSRs are found to be highly polymorphic exhibiting different alleles among closely related individuals for each marker in relatively lesser time and minute quantity of DNA which is in agreement with recent reports in pigeonpea ( Bohra et al, 2015 , 2017 ). The SSR has been employed extensively in sorghum to study genetic diversity, linkage mapping and QTL analysis ( Njung’e et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the SSRs are found to be highly polymorphic exhibiting different alleles among closely related individuals for each marker in relatively lesser time and minute quantity of DNA which is in agreement with recent reports in pigeonpea ( Bohra et al, 2015 , 2017 ). The SSR has been employed extensively in sorghum to study genetic diversity, linkage mapping and QTL analysis ( Njung’e et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, resistance to wilt is an essential prerequisite for variety identification and release in pigeonpea. Several pigeonpea varieties such as Asha (ICPL , 1998;Castillo et al, 2003 Chickpea Andoum 1 and Ayala (race 0) - Halila and Harrabi, 1990;Landa et al, 2006 Chickpea Surutato-77, Sonora-80, Tubutama, UC-15 and UC-27, Gavilan Mexico Morales, 1986;Buddenhagen et al, 1988;Helms et al, 1992;Sharma et al, 2005 Chickpea (Singh I. P. et al, 2016;Bohra et al, 2017).…”
Section: Plant Genetic Resources For Fw Resistancementioning
confidence: 99%
“…Like other crop plants, molecular markers have been proved to be most effective in evaluating genetic diversity, structure analysis and phylogenetic relatedness among rice accessions too [10,36]. During recent years, SSR markers based genotyping has proven to be very useful for exploring a variety of surreptitious information in plants, ranging from domestication traits to crop improvement through marker-assisted breeding [37][38][39][40]. Although, individual reports on micronutrient density and SSR based genetic diversity in rice have been recently published [10,12,13,36,41], however, to date, a combined study of grain Fe and Zn contents and trait linked SSR markers based genetic diversity is obscure.…”
Section: Discussionmentioning
confidence: 99%